If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -7x + 3x = -7 Combine like terms: -7x + 3x = -4x -7 + -4x = -7 Add '7' to each side of the equation. -7 + 7 + -4x = -7 + 7 Combine like terms: -7 + 7 = 0 0 + -4x = -7 + 7 -4x = -7 + 7 Combine like terms: -7 + 7 = 0 -4x = 0 Solving -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-4'. x = 0 Simplifying x = 0
| 5x+-4=2x+3 | | 6y(8y-4)=22 | | -21-(-8)= | | -h+7h= | | t-49=-32 | | x-(x/10)=-3 | | Solvex+14.91=59.67 | | 11=x+5+2x | | -209=5x-6(5x+14) | | 11=x+5+2 | | 2x-16=84 | | x-x/10=-3 | | 2j=10.56 | | 3(x+4)-5(x-4)=2x+4(x-6) | | -5+6m-4m= | | 6=3k | | -13-2(4-3x)=-12 | | -16=p+3p | | q+10.3=15 | | 7(2x-1)-3x=x-17 | | -4(2x-1)-2x-1=2 | | 2m=5.8 | | -3(6-8n)=-186 | | (3x-7)+(14x-2)= | | 7x-x=21 | | 20x-30x-20=4x-6 | | -6+(-15)= | | 6+6k-k=-14 | | 62-11(3-4x)=15 | | 7x-21=y | | 4(x-3)-18=16 | | 62-11(3-4x)=-5 |